Fertilizer policy in India: An overview - Gupta, Surupa (International Food Policy Research Institute, 2011)
The debate on fertilizer subsidy, as well as all other agricultural subsidies in India, should be examined against the backdrop of India's overall economic situation, the prominence of farmers and the agricultural sector in India's political economy, and recent trends in the Indian agricultural economy. This chapter presents socioeconomic data on the Indian economy, particularly its farm sector, and discusses issues related to fertilizer production and use. Table 4.1 provides an overview of the growth rate, holding size, and indebtedness of the farm sector in India.